2018
DOI: 10.1155/2018/4751627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Post-Resin Matrix Composition on Bond Strength of Post-Cement Interface

Abstract: Objective To evaluate the influence of 3 different post-resin matrix systems cemented with dual-cure resin cement in simulated root canals made of PMMA acrylic sheet. Methods 3 types of fiber posts (n = 60) with different resin matrixes divided into 3 groups: group 1 cross-linked FRC Postec Plus post (n = 20), group 2 cross-linked Rely X post (n = 20), and group 3 Interpenetrated IPN Everstick post (n = 20). All posts were cemented using Multilink Automix dual-cure cement. Posts were cemented into acrylic bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This indicates that stronger adhesion has occurred between Parapost FiberLux posts with both types of luting cement used, as compared to GC everStick ® POST. In agreement with this result, a previous study by Alnaqbi et al ( 33 ) has also found that the everStick ® POST recorded a lower bond strength than RelyX Fiber post. Another previous study has also obtained a similar result where RelyX Fiber post has a higher bond strength when cemented with RelyX TM Unicem than that recorded of GC everStick ® POST when cemented with similar types of luting cements ( 34 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This indicates that stronger adhesion has occurred between Parapost FiberLux posts with both types of luting cement used, as compared to GC everStick ® POST. In agreement with this result, a previous study by Alnaqbi et al ( 33 ) has also found that the everStick ® POST recorded a lower bond strength than RelyX Fiber post. Another previous study has also obtained a similar result where RelyX Fiber post has a higher bond strength when cemented with RelyX TM Unicem than that recorded of GC everStick ® POST when cemented with similar types of luting cements ( 34 ).…”
Section: Discussionsupporting
confidence: 87%
“…Another previous study has also obtained a similar result where RelyX Fiber post has a higher bond strength when cemented with RelyX TM Unicem than that recorded of GC everStick ® POST when cemented with similar types of luting cements ( 34 ). There are several mechanisms that contribute to the adhesion between the fiber posts and resin cements, and these include micromechanical interlocking, chemical bonding and inter-diffusion ( 33 ). The high elasticity properties of fiber-reinforced posts make the strain generated to be greatly reduced ( 35 ) and also provides the post with similar physical properties as natural dentin ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, several compositions of experimentally laboratory-mixed urethane-dimethacrylate (UDMA, 90%)-methyl-methacrylate (MMA, 10%) monomer-based resin were prepared. Presently, several kinds of monomers are applied in dental practice, for example, Bis-GMA, TEGDMA and UDMA [ 21 , 22 ]. Of these, an UDMA-MMA based monomer system was used.…”
Section: Discussionmentioning
confidence: 99%
“…Hence the longevity of the customized post depends on the adhesive ability. [15] The matrix present in GFP has epoxy resin [16] , owing to their highly cross linked structure, they cannot chemically bond with composite. [17] According to Valdiviya et al, surface treatment of GFP increased the bond strength of GFP to root dentine.…”
Section: Discussionmentioning
confidence: 99%